An Efficient and Large Scale Process for Synthesis of Valacyclovir Dr. Reddy’s Communication No. IPDO IPM-00156 - Prasada Raju, V.V.N.K.V.; Vedantham, Ravindra; D. Khunt, Mayur; T. Mathad, Vijayavitthal; K. Dubey, Pramod; Kalyan Chakravarthy, Akula (Asian Journal of Chemistry, 2010)
A facile, commercially viable and large scale process is developed for an antiviral drug substance, valacyclovir hydrochloride. Several process related critical factors including organic and heavy metal impurities are efficiently addressed in this process.